Pre-saccadic remapping relies on dynamics of spatial attention - Martin Szinte; Donatas Jonikaitis; Dragan Rangelov; Heiner Deubel (eLife, 2018)
Each saccade shifts the projections of the visual scene on the retina. It has been proposed that the receptive fields of neurons in oculomotor areas are predictively remapped to account for these shifts. While remapping of the whole visual scene seems prohibitively complex, selection by attention may limit these processes to a subset of attended locations. Because attentional selection consumes time, remapping of attended locations should evolve in time, too. In our study, we cued a spatial location by presenting an attention-capturing cue at different times before a saccade and constructed maps of attentional allocation across the visual field. We observed no remapping of attention when the cue appeared shortly before saccade. In contrast, when the cue appeared sufficiently early before saccade, attentional resources were reallocated precisely to the remapped location. Our results show that pre-saccadic remapping takes time to develop suggesting that it relies on the spatial and temporal dynamics of spatial attention.